2018
DOI: 10.1097/meg.0000000000001083
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a scoring index to predict the presence of lesions in capsule endoscopy in patients with suspected Crohn’s disease of the small bowel: a Spanish multicenter study

Abstract: Results from the internal validation process show that the scoring index is coherent, and results from the external validation process confirm its reliability. This index can be a useful tool for selecting patients before CE studies in cases of suspected CD of the small bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Symptoms alone are a poor predictor of CD. The International Conference on Capsule Endoscopy (ICCE) [117] recommended a broader definition of suspected CD that includes inflammatory markers, abnormal imaging, and/or extraintestinal manifestations [118,119]. It has also been demonstrated that ICCE criteria can be used as an effective selection tool for SBCE since patients with fewer than two ICCE criteria are not only unlikely to have inflammatory changes in the small bowel but also to be diagnosed with CD in the follow-up [118].…”
Section: Recommendationmentioning
confidence: 99%
“…Symptoms alone are a poor predictor of CD. The International Conference on Capsule Endoscopy (ICCE) [117] recommended a broader definition of suspected CD that includes inflammatory markers, abnormal imaging, and/or extraintestinal manifestations [118,119]. It has also been demonstrated that ICCE criteria can be used as an effective selection tool for SBCE since patients with fewer than two ICCE criteria are not only unlikely to have inflammatory changes in the small bowel but also to be diagnosed with CD in the follow-up [118].…”
Section: Recommendationmentioning
confidence: 99%
“…1 Score ranges 0 to 5, 6 to 15, and ≥16 predicted low, intermediate, and high risk of inflammatory lesions on VCE, respectively. 61…”
Section: Resultsmentioning
confidence: 99%
“…1 Score ranges 0 to 5, 6 to 15, and !16 predicted low, intermediate, and high risk of inflammatory lesions on VCE, respectively. 61 Another elegant study has shown the incremental yield of VCE with an increasing number of International Conference on Capsule Endoscopy (ICCE) criteria. Suspected CD was defined as clinical symptoms (chronic abdominal pain/diarrhea, weight loss, and growth failure) plus any one or more extraintestinal manifestations, inflammatory markers, and abnormal imaging (SBFT/CTE).…”
Section: Factors Affecting Yield Of Video Capsule Endoscopy In Suspec...mentioning
confidence: 99%